Modernizing English Teacher Education in Chile: A Case Study from a Southern University - Gómez Burgos, Eric; Walker, Wanda (Colombian Applied Linguistics Journal, 2020)
Initial teacher education programmes for future English teachers in Chile have been in the spotlight and under constant analysis in the last decade. The main reasons are the new demands of a globalised world, the current undergraduate programmes in the area that present a constant divorce between English and pedagogy and the consistently low student achievement outcomes on the standardised tests applied by the educational system. Under the previous considerations, this work reports on a pedagogical experience of implementing a new proposal for English teacher preparation offered by a university from the south of Chile. This innovative new teacher education programme is based on the following three important components: (1) the competency-based model adopted by the university, (2) the integration of the content and pedagogical knowledge in the programme and (3) the adoption of an immersion programme focussed on content and language integration. The data gathering and analysis comprise documents and pre-mid-point progress tests. The preliminary results show a marked improvement in the level of students’ English and an increase in their acquisition of the pedagogical concepts. Whilst minor changes are crucial to improve some aspects of the programme proposal, the overall results are promising.